Approaches to sustainable tourism development associated with community empowerment. Systematic literature review - Hernández Valdés, Leisa; Rodríguez Cairo, Vladimir; Iglesias Leon, Silvia; Gutiérrez Oblitas, Adriana Isabel (Revista Venezolana de Gerencia, 2025)
The research provides a comprehensive analysis of the most widely used approaches to sustainable tourism development associated with community empowerment. The study combined a bibliometric analysis and a systematic literature review of articles indexed in the Scopus database. Predefined inclusion and exclusion criteria were applied, identifying 61 articles published between 2018 and 2025, of which 54 were deemed relevant to the objectives of the study. The bibliometric analysis was conducted using the Bibliometrix – Biblioshiny tool, enabling the statistical processing of metadata and facilitating the interpretation of patterns and trends in the scientific literature. The main result is that the predominant approaches to sustainable tourism development associated with community empowerment are the top-down approach, which implies greater intervention by the State or actors outside the community; and the bottom-up approach, which encourages community participation in the management of their resources and assets. It is concluded that the bottom-up approach is considered more conducive to achieving community empowerment, as it allows local communities to actively participate in decision making, ensuring that their needs and aspirations are considered in the development process.